2015
DOI: 10.1007/s10517-015-2937-2
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Effects on Survival of Human Multiple Myeloma Cells

Abstract: Insulin effects of human multiple myeloma cell survival were studied on RPMI1640, RPMI8226, and IM9 lines differing by differentiation degree. The effects of exogenous insulin on tumor cell growth and survival varied. Insulin alone did not improve the viability of myeloma cells, while in combination with serum growth factors increased it. The IM9 cells with immunophenotype (CD(138+), CD(38-), CD(45+), CD(56-), CD(19+)) exhibited the highest sensitivity to serum growth factors, while RPMI1640 and RPMI8226 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Also was shown that functional insulin receptors are preferentially expressed in multiple myeloma cell lines compared to B-lymphoblastoid cell lines [21]. Earlier, we have shown that INS affects the survival of human MM cells [22]. Our current work established that INS has a dual impact on MM cells: INS is really a growth factor for MM cells, but on the other hand, it is an inducer of cell death.…”
Section: Introductionsupporting
confidence: 55%
“…Also was shown that functional insulin receptors are preferentially expressed in multiple myeloma cell lines compared to B-lymphoblastoid cell lines [21]. Earlier, we have shown that INS affects the survival of human MM cells [22]. Our current work established that INS has a dual impact on MM cells: INS is really a growth factor for MM cells, but on the other hand, it is an inducer of cell death.…”
Section: Introductionsupporting
confidence: 55%